Feeding practices and prevalence of early childhood caries among preschool children in urban and rural areas of Kannur district - Sreedharan, Aswathi; CP, Faizal; TP, Chandru (International Journal of Dental Research, 2016)
Background: Early childhood caries (ECC) is one of the most prevalent chronic conditions among children. Lack of proper Parental knowledge regarding feeding practices will have a deleterious effect on child oral health.Objective: The purpose of the study was to assess the prevalence of ECC and parental knowledge regarding feeding practices in young children.Methods: 500 preschool children aged between 36-60 months, were selected from twenty schools. The children’s were examined at the respective schools to determine the presence or absence of caries by using WHO criteria .A structured questionnaire was provided to 500 parents of the respective school children examined to assess their knowledge regarding feeding practices and oral hygiene measures in preschool children for prevention of ECCResult: The results of the children examined and the parent surveyed were tabulated and statistically analyzed by using chi-square test. The result showed that the prevalence rate of ECC among 500 children surveyed were about 56.3%.The knowledge regarding the feeding practices and oral hygiene measures overall was found to be 56.5%Conclusion: The prevalence of ECC was relatively high among the preschool children. The feeding practices and oral hygiene measures among parents was more off supporting the promotion of ECC. More emphasis should be given regarding introduction of oral hygiene practice from the first year of child’s life and also to conduct public awareness programme to achieve optimum oral health care in children.